Alternative Locations for Final Processing Sites (TPA) Based on Geographic Information Systems in Jember Regency: Penentuan Alternatif Lokasi Tempat Pemrosesan Akhir (TPA) Berbasis Sistem Informasi Geografis di Kabupaten Jember - Pangestuti, Ajeng; Badriani, Ririn Endah; Listyawati, Ratih Novi (MATRAPOLIS: Jurnal Perencanaan Wilayah dan Kota, 2025)
Jember Regency is a region located in East Java that is currently experiencing continuous population growth each year. This increase has a direct impact on the volume of waste generated. One of the resulting issues is the continued use of an outdated Final Processing Site (TPA), which causes disturbances to nearby communities, including air pollution and potential disease transmission. The overcapacity condition of the TPA, with waste piles reaching approximately 25 meters high, poses a serious threat to the environment if not addressed properly. Therefore, this study was conducted to identify alternative locations for a new TPA that meet technical, social, and environmental feasibility criteria within the Jember area. The study also examines the current waste management characteristics in the region to support a more efficient and sustainable waste management system. The methods used include Descriptive Analysis, Analytical Hierarchy Process (AHP), and GIS-based Weighted Overlay Analysis. AHP was applied to determine the weight and priority of each criterion in the TPA site selection process, which then served as input for the Weighted Overlay Analysis to generate potential locations. Based on the analysis results, Jombang District and Ajung District were identified as the most suitable areas for the development of a new TPA. The findings of this study are expected to serve as a reference for determining more appropriate and data-driven TPA site selections in Jember Regency.